734 Prevalence and Correlates of Insomnia in Veterans with and without Military Sexual Trauma Receiving Care within a VA Med Center. (3rd May 2021) - Makar, Karen; Rivera, Louis; Mazur, Rena; Aguiar, Taylor; Krouse, Ryan; Chakravorty, Subhajit
Abstract: Introduction: A prior study showed a higher prevalence of insomnia among younger Veterans with military sexual trauma (MST) before receiving care at a VA Medical Center (VAMC). We extend the literature to investigate the prevalence and correlates of insomnia in male Veterans with and without MST currently receiving care within a VAMC. Methods: We evaluated cross-sectional data from a survey within the Philadelphia VAMC (N=138) using the following instruments: Insomnia Severity Index (ISI) total score for insomnia; Sexual Harassment Scale (DRRI-2) to screen for MST; PTSD checklist for DSM-5 (PCL-5) PTSD symptoms; Quick Inventory of Depressive Symptomatology-Self report (QIDS-SR) to evaluate depressive symptoms; Alcohol Use Disorder Identification Test (AUDIT-C) to assess for harmful drinking; and, the nightmare question from the PCL-5 scale to screen for persistent nightmares. The association between ISI total score and variables were assessed separately in individuals with and without MST, using bivariate and multivariable analyses. Results: The mean(SD) age was 55.2(12.8) years. They were likely to identify themselves as African-American (44.2%), and had a high school diploma (39.1%). MST was endorsed by 31.9% of the Veterans. Insomnia was more prevalent in those with MST [N=42(95.4%)] than those without [N=77(81.9%)]. Individuals with MST had higher ISI (19.9±5.0 Vs 16.7±7.2) and PCL-5 (48.4±14.4 Vs 38.1±19.7) total scores, than individuals without. Among those with MST, the bivariate analysis showed significant associations with PCL-5 (β=0.2, p<0.0001), QIDS (β=0.5, p=0.01), AUDIT-C (β=0.5, p=0.008), and nightmares (β=3.9, p=0.03). In the multivariable model, ISI total score was only associated with the PCL-5 total score (β=0.3, R2=0.18, p=0.0005). Among those without MST, the bivariate analysis showed significant associations between ISI total score and age (β=-0.1, p=0.02), total scores on the PCL-5 (β=0.2, p<0.0001), QIDS (β=0.9, p<0.00001), and nightmare (β=6.7, p<0.0001). In the multivariable model (R2=0.5, p<0.00001), the ISI total score was associated with PCL-5 (β=0.1, p=0.01), and QIDS (β=0.7, p=<0.0001) total scores. Conclusion: There is a higher prevalence of insomnia among Veterans with MST currently receiving care within the VHA. Treatment of insomnia and PTSD is critical to improve their well-being and prevent complications. Support (if any): The study was supported by VA grant IK2CX000855 (S.C.).